Exploration of pulse wave analysis under reactive hyperemia and close to an arteriovenous fistula: a comparative analysis - Busch, Veit; Müller, Sandra; Streis, Joachim; Westhoff, Timm H.; Felderhoff, Thomas; Seibert, Felix S.; Reuter, Stefan; Mueller, Niklas (BMC cardiovascular disorders, 2025)
Analyzing novel pulse wave parameters, we aimed to study specific changes in pulse waveform under high flow conditions in three collectives (i.e., healthy individuals and two collectives of patients with kidney disease and different levels of comorbidities): First, under reactive hyperemia in order to assess endothelial function. Second, close to an ateriovenous fistula in order to assess fistula function. Subjects underwent local peripheral tonometric pulse wave analysis with the SphygmoCor® device and duplex sonography to assess flow velocity (peak V and diastolic V ) under physiological conditions. Corresponding measurements were then performed under reactive hyperemia and at fistula arms. The area under the curve and the mean slope between the systolic peak and the end of systole of pulse waves and duplex flow velocities were analysed as parameter differences under high flow and physiological conditions (∆A2 and ∆m2, ∆V and ∆V ). In addition, the augmentation index was evaluated (only) under physiological conditions. The Wilcoxon test was used to assess parameter differences and linear correlation was performed. A total of 108 subjects were evaluated (23 healthy and 85 with fistula in two distinct collectives n = 39/45, measurements under reactive hyperemia in 62 individuals). Significant increments in the novel pulse parameters were observed under reactive hyperemia and near a fistula and were found to correlate with corresponding changes in flow velocity (reactive hyperemia: ∆A2 and ∆m2/V r = 0.347, p = 0.006 and r = 0.374, p = 0.003; fistula: ∆A2/∆V r = 0.315, p = 0.003, no significant correlation for ∆m2/V ). Consistent with their different vascular status and endothelial function, changes in pulse wave parameters during reactive hyperemia were significantly different in patients and healthy subjects. Both high flow conditions induced similar changes in the pulse waveform and a delay of the systolic peak in all three collectives. The augmentation index was different in the three collectives and correlated with the increase of the novel parameters and the peak flow velocity under reactive hyperemia: ∆A2 r = 0.445, p < 0.001, ∆m2 r = 0.338, p = 0.007, ∆V r = 0.460. Detection of changes in pulse waveform under high flow conditions is potentially a new clinical application to characterize endothelial function and the functional status of ateriovenous fistulas.